DETERMINANTS OF ENTREPRENEURIAL INVESTMENTS IN PRIVATE SECTOR HEALTH SERVICES PROVISION IN WOTE, MAKUENI COUNTY - Musyoka, Fredrick Kaati; Ombui, Dr. Kepha; Iravo, Dr. Mike (International Journal of Entrepreneurship and Project Management, 2017)
Purpose: To establish the determinants of entrepreneurial investments in private sector health services provision in Wote, Makueni County. Methodology: The study utilized a descriptive research design. Findings: Results showed that economic incentives, existence of private capital, qualified medics and practitioners and purchasing power of the local population influences entrepreneurial investment in private sector health service provision in Wote, Makueni County. The study concluded that economic incentives, existence of private capital, qualified medics and practitioners and purchasing power of the local population influences entrepreneurial investment in private sector health service provision in Wote, Makueni County. Unique contribution to theory, practice and policy: The study will add to the body of knowledge on the factors that affect private entrepreneurs from investing in quality health services in the Makueni County and how can those hindering factors be overcome. The study results will be an addition to the body of knowledge, useful to researcher and academicians alike. The study findings will be beneficial to the private sector entrepreneurs who upon getting the factors that affect investing in the health sector in Makueni County will be able to address those factors and get involved in investing in this lucrative health sector at the county level. Furthermore, the study will provide valuable information to not only the national government but the more so the county government and by using the findings the county government will draw up favourable policies that will stimulate private sector involvement in the establishment of quality health care services and other incentives that can spur county economic growth.